Enhanced fine soil aggregation and organic matter accumulation facilitated by Salix Psammophila sand barriers along desert highways - Zhao, Chen; Gao, Yong; Han, Yanlong; Yang, Xiaojie (Frontiers in Environmental Science, 2025)
Desert ecosystems are inherently nutrient-limited and highly susceptible to disturbances. In such arid environments, sand barriers play a pivotal role in ecological restoration efforts. Despite their importance, the long-term effects of Salix Psammophila sand barriers on soil particle size distribution and organic matter content in the Hobq Desert, China, have received limited empirical investigation. To this end, the present study was conducted to investigate sand dunes along the Hobq Desert Sand Penetration Highway, where sand barriers had been established for 1, 3, and 5 years. Specifically, soil particle size distribution was analyzed using multifractal theory to assess spatiotemporal variations associated with varying durations of sand barriers installation. The following observations should be noted: Ⅰ. Significant differences were identified in soil particle size distribution between dunes with varying sand barrier ages and mobile dunes within the study area. As the duration of sand barriers presence increased, the proportions of clay (3.45%), silt (5.46%), and very fine sand (7.35%) increased correspondingly, whereas the fractions of medium and coarse sand decreased. Ⅱ. Multifractal spectral analysis of soil particle size distribution enabled the precise quantification of soil texture heterogeneity. Over time following the installation of sand barriers, soil particle size distribution exhibited enhanced heterogeneity, evidenced by an expanded spectrum and increased fine-grained material content. Ⅲ. Soil organic matter content increased substantially with the duration of sand barriers establishment. Notable spatial variations in organic matter content were detected across different dune slopes, following the trend: bottom slope (0.85 kg/kg) > middle slope (0.77 kg/kg) > top slope (0.62 kg/kg). Moreover, soil particle size distribution exhibited a strong correlation with soil organic matter content, suggesting the essential role of clay, silt, and very fine sand in organic matter stabilization. Collectively, the installation of Salix Psammophila sand barriers significantly enhances the accumulation of fine soil fractions (clay, silt, and extremely fine sand), thereby facilitating the sequestration of soil organic matter. This process improves soil physicochemical properties, fosters vegetation establishment, and ensures the long-term stabilization of aeolian landforms along desert highways.